Advancements in clinical approaches, analytical methods, and smart sampling for LC–MS‐based protein determination from dried matrix spots - Reubsaet, Léon; Halvorsen, Trine Grønhaug (Journal of separation science, 2024)
Determination of proteins from dried matrix spots using MS is an expanding research area. Mainly, the collected dried matrix sample is whole blood from a finger or heal prick, resulting in dried blood spots. However as other matrices such as plasma, serum, urine, and tear fluid also can be collected in this way, the term dried matrix spot is used as an overarching term. In this review, the focus is on advancements in the field made from 2017 up to 2023. In the first part reviews concerning the subject are discussed. After this, advancements made for clinical purposes are highlighted. Both targeted protein analyses, with and without the use of affinity extractions, as well as untargeted, global proteomic approaches are discussed. In the last part, both methodological advancements are being reviewed as well as the possibility to integrate sample preparation steps during the sample handling. The focus, of this so‐called smart sampling, is on the incorporation of cell separation, proteolysis, and antibody‐based affinity capture.